Sosialisasi dan Pendampingan Belajar Siswa Sekolah Dasar Melalui Program Kuliah Kerja pada Masa Pandemi Covid-19 di Jember - Didik Sugeng Pambudi; Tyas Adinda Novitasari; Siti Shofiya (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The Covid 19 pandemic that has occurred since March 2020 until now has affected educational activities and campus life. All students, including elementary school (SD) students are forced to study independently at home, causing learning difficulties, especially in mathematics. In addition, there are still many elementary students who have not implemented health protocols. This community service activity aims to provide socialization and learning assistance to elementary students through the Jember University FKIP Student Work Lecture program regarding the Covid-19 health protocol material, and mathematics subjects. This activity was carried out in September 2020 using a combination of on line and off line methods. The online method is carried out by using the zoom platform for mentoring activities between the supervisor and students. The offline method is carried out by students with community service participants through the methods of lectures, demonstrations, question and answer, observation, and interviews. The community service participants are elementary school students who need learning assistance in Ambulu and Sukorambi sub-districts, Jember regency. Place of activity in local people's homes. All participants actively participated in the activities and were able to achieve excellent performance, namely (1) the practice of washing hands with soap, wearing masks, and maintaining distance, and (2) being able to solve elementary math problems well. Students and parents gave very positive responses to the implementation of learning assistance activities, because they have provided benefits to students regarding health protocols and mastery of mathematics material.